A STUDY ON THE ABILITY OF THE THIRD YEAR STUDENTS OF MAN 1 PEKANBARU IN COMPREHENDING SPOOF TEXTS - Triyana, Ade; Delfi, Syofia; ', Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This descriptive research was aimed to find out the ability of the third year students of MAN 1 Pekanbaru in comprehending spoof texts. The research data were collected on November 2016. The subject of this research was class XII Social 1 which consisted of 32 students. The data were collected by administering a test to the students in the form of multiple choice test. The test consisted of 40 items. Based on the research, it was found out that first: the ability of the third year students in reading comprehension was classified into good level with the mean score of 68,83. Second, the students’ mean score in finding main ideas was classified into mediocre level with the mean score of 43, finding the factual information in event was classified into excellent level with the mean score of 93, factual information in twist was classified into good level with the mean score of 66, in finding the meaning of vocabulary was classified into good level with the mean score of 67,18 , in finding references was classified into excellent level with the mean score of 83, in finding inferences was classified into mediocre level with the mean score of 55, in finding social function was classified into good level with the mean score of 78. As a conclusion, the highest score obtained by the students was in finding factual information in event with the mean score of 93 which categorized into excellent level, and the lowest score was in finding main ideas with the mean score of 43 which categorized into mediocre level. It is recommmended that the students must do more practice and read books to improve reading skills, especially in finding main ideas, because the students got the lowest score in that term. Next, the teacher should have more effort to develop the students’ motivation and encourage them to practice in comprehending the text. The last, other researcher are recommmended to conduct another research design about spoof text.Keywords: Reading Ability, Comprehending Spoof Texts.